Klinični pomen gleženjskega indeksa - Šabovič, Mišo (Medicinski razgledi, 2003)
The ankle-brachial index is the ratio between systolic arterial pressures measured on the arms and the ankles. It is a highly sensitive and specific test for detecting peripheral arterial occlusive disease (PAOD). Decreased ABIis a marker of PAOD progression; it predicts complications of PAOD and mortality. ABI correlates well with the presence of coronary and cerebrovascular atherosclerosis. Therefore, it is a good non-invasive surrogate marker of (coronary) atherosclerosis. It is clinically relevant thatpatients with decreased ABI have an increased risk of cardiovascular events and mortality. Furthermore, decreased ABI measured in elderly persons is associated with disturbed mobility and gait not directly associated with intermittent claudication. Overall, it appears that ABI, due to its simplicityand a high predictive value, should become a routine test (along with the standard risk factor assessment) for estimating cardiovascular risk. It makes sense that in case a decreased ABI is found, measures to retard further progress of atherosclerosis should be applied.
Keywords: Arterial Occlusive Diseases; Arterijske, okluzivne bolezni; Diagnosis; Gleženj; Krvni pritisk; Blood Pressure; Zgornji ud; Arm; Ankle; ateroskleroza; meritve; diagnostika